(3x-4)/(2x-3)=(x-16)/(x-9)

Simple and best practice solution for (3x-4)/(2x-3)=(x-16)/(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-4)/(2x-3)=(x-16)/(x-9) equation:


D( x )

2*x-3 = 0

x-9 = 0

2*x-3 = 0

2*x-3 = 0

2*x-3 = 0 // + 3

2*x = 3 // : 2

x = 3/2

x-9 = 0

x-9 = 0

x-9 = 0 // + 9

x = 9

x in (-oo:3/2) U (3/2:9) U (9:+oo)

(3*x-4)/(2*x-3) = (x-16)/(x-9) // - (x-16)/(x-9)

(3*x-4)/(2*x-3)-((x-16)/(x-9)) = 0

(3*x-4)/(2*x-3)+(-1*(x-16))/(x-9) = 0

((3*x-4)*(x-9))/((2*x-3)*(x-9))+(-1*(x-16)*(2*x-3))/((2*x-3)*(x-9)) = 0

(3*x-4)*(x-9)-1*(x-16)*(2*x-3) = 0

x^2+4*x-12 = 0

x^2+4*x-12 = 0

x^2+4*x-12 = 0

DELTA = 4^2-(-12*1*4)

DELTA = 64

DELTA > 0

x = (64^(1/2)-4)/(1*2) or x = (-64^(1/2)-4)/(1*2)

x = 2 or x = -6

(x+6)*(x-2) = 0

((x+6)*(x-2))/((2*x-3)*(x-9)) = 0

((x+6)*(x-2))/((2*x-3)*(x-9)) = 0 // * (2*x-3)*(x-9)

(x+6)*(x-2) = 0

( x+6 )

x+6 = 0 // - 6

x = -6

( x-2 )

x-2 = 0 // + 2

x = 2

x in { -6, 2 }

See similar equations:

| 3(x-2)=34-5x | | 7*5+ab=25+7a | | 2n-20=10 | | x^2+4x+84=0 | | 8(x+3)=2(x-36) | | 20-2n=10 | | a+b=a-b | | 8(3-y)=2+3y | | 4p+3r+7-p+2r-6= | | 5.7x=3 | | 47-6x=12x-15 | | 1/2=12x | | z=3x+8y | | (3x+8)/(8x-2)-(x+8)/(8x-2) | | 2ln(x-6)=0 | | (6y-7)/(6y+7) | | 18a+72= | | 5x+127=12x-6 | | 8m-14=3m+16 | | -56-8x+8x+24= | | 2c-5=b+23 | | 100-5h=0 | | 5(a-1)=10 | | 7y+4b=25+4*7-by | | 2n+7=5n-n | | 20-2g=6 | | 5x-3=12-52 | | 28-(-18)/-2-15(-2)(-6)/3 | | 7x+12=95+x | | 7x+12=95+3 | | 3x-1/4-5=x/2+1 | | 7y+bx=25+7x-by |

Equations solver categories